"[Women] should be helpmates and not drags upon their husbands": Female education in Brooke Sarawak, 1841-1941. - Ooi, Keat Gin (1996)
The provision of education was not given serious consideration by the Brookes, and it was to the credit of Christian missionaries and the Chinese community that schools were started and education developed during this period.